2019
DOI: 10.1002/jcb.29472
|View full text |Cite
|
Sign up to set email alerts
|

LINC00958 facilitates cervical cancer cell proliferation and metastasis by sponging miR‐625‐5p to upregulate LRRC8E expression

Abstract: Accepted as a malignant tumor worldwide, cervical cancer (CC) has attracted much attention for its high incidence and mortality rates. Previous studies have elucidated the critical regulatory function that long noncoding RNAs (lncRNAs) exert on the tumorigenesis and progression of diverse tumors. Although multiple investigations have depicted that LINC00958 has a great impact on the complex biological process of many cancers, knowledge concerning the regulatory role of LINC00958 in CC remains limited and needs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…An increasing amount of evidence suggests that dysregulation of lncRNAs are closely implicated in the pathogenesis, development and metastasis of CRC (22,23). Emerging evidence confirms that LINC00958 expression is notably overexpressed in cervical cancer cells, and LINC00958 contributes to the proliferation and metastasis of cervical cancer cells (24). In support, a previous study highlighted the importance of LINC00958 in the occurrence of glioma (25).…”
Section: Discussionmentioning
confidence: 85%
“…An increasing amount of evidence suggests that dysregulation of lncRNAs are closely implicated in the pathogenesis, development and metastasis of CRC (22,23). Emerging evidence confirms that LINC00958 expression is notably overexpressed in cervical cancer cells, and LINC00958 contributes to the proliferation and metastasis of cervical cancer cells (24). In support, a previous study highlighted the importance of LINC00958 in the occurrence of glioma (25).…”
Section: Discussionmentioning
confidence: 85%
“…Several studies have suggested that lncRNAs, including BLACAT2, regulates cancer progression by sponging miRNAs. For instance, BLACAT2 has been shown to facilitate cervical cancer cell proliferation and metastasis by sponging miR-625-5p, which upregulates the expression of LRRC8E [23]. Similarly, it was verified that the silencing of BLACAT2 prevents tumor initiation of pancreatic cancer by acting as a sponge of microRNA-330-5p to down-regulate PAX8 [24].…”
Section: Discussionmentioning
confidence: 95%
“…A recent study showed that LINC00958 is involved in the carcinogenesis of bladder cancer [12]. The high expression of LINC00958 has also been shown to promote the occurrence and development of certain cancers, including bladder cancer, oral cancer, pancreatic cancer, gastric cancer, cervical cancer and glioma [13][14][15][16][17][18]. However, the relevant mechanism of LINC00958 in EC, especially ESCC, has not yet been determined.…”
Section: Introductionmentioning
confidence: 99%